2011
DOI: 10.1007/s10488-011-0353-0
|View full text |Cite
|
Sign up to set email alerts
|

Are Children Improving? Results from Outcome Measurement in a Large Mental Health System

Abstract: Standardized outcome assessment was implemented in a large county mental health system. This study examines changes in children's emotional and behavioral problems after 6 months of treatment and identifies factors associated with treatment improvement. Results from 3,215 youth indicated that externalizing and internalizing problems significantly decreased from intake to 6 months and that ethnicity, gender, and age were associated with caregiver-reported changes in symptomatology. While there was improvement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Several studies have reported aggregate decreases in children’s behavioral and emotional problems after entering care in community-based service systems, reflecting overall improvement in symptoms (Hawley and Weisz 2005; Manteuffel et al 2002; Trask and Garland 2011), but like all uncontrolled studies, the extent to which these observed changes can be attributed to treatment received is unknown. Results from a number of studies demonstrating no “dose–effect” relationship (i.e., no link between amount of treatment received—usually measured as number of sessions attended—and outcome variability) reinforce skepticism about attributing observed symptom change to treatment (Andrade et al 2000; Garland et al Under Review; Lindhiem and Kolko 2011; Trask and Garland 2011; Warren et al 2009).…”
Section: The Problem: Ineffectiveness Of Usual Mental Health Care Formentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported aggregate decreases in children’s behavioral and emotional problems after entering care in community-based service systems, reflecting overall improvement in symptoms (Hawley and Weisz 2005; Manteuffel et al 2002; Trask and Garland 2011), but like all uncontrolled studies, the extent to which these observed changes can be attributed to treatment received is unknown. Results from a number of studies demonstrating no “dose–effect” relationship (i.e., no link between amount of treatment received—usually measured as number of sessions attended—and outcome variability) reinforce skepticism about attributing observed symptom change to treatment (Andrade et al 2000; Garland et al Under Review; Lindhiem and Kolko 2011; Trask and Garland 2011; Warren et al 2009).…”
Section: The Problem: Ineffectiveness Of Usual Mental Health Care Formentioning
confidence: 99%
“…Results from a number of studies demonstrating no “dose–effect” relationship (i.e., no link between amount of treatment received—usually measured as number of sessions attended—and outcome variability) reinforce skepticism about attributing observed symptom change to treatment (Andrade et al 2000; Garland et al Under Review; Lindhiem and Kolko 2011; Trask and Garland 2011; Warren et al 2009). Lambert and Bickman (2004) proposed that observed decreases in symptom severity and/ or improvements in functioning after service entry should not necessarily be attributed to service effectiveness because such changes likely reflect predictable variation, including expected “regression to the mean.” Longitudinal modeling of expected variations in symptom severity and the assumption that children generally enter care when symptoms are most severe support this point.…”
Section: The Problem: Ineffectiveness Of Usual Mental Health Care Formentioning
confidence: 99%
“…Other clinical literature has found that initial behavioral health needs are often significant predictors of behavioral health needs at multiple follow-up points (e.g. Trask and Garland 2012). This may be related to the very small overall mean change in behavioral health needs score from initial assessment to 6 month assessment (see Table 1; youth in this sample experienced a .6 point reduction in behavioral health needs and had a .nine point gain in resources over 6 months of treatment).…”
Section: Discussionmentioning
confidence: 75%
“…Given discouraging data regarding the limited effectiveness of routine mental health care for children (Trask & Garland, 2012; Weisz & Jensen, 2001; Weisz, 2004), there have been numerous national calls for improved dissemination and implementation of evidence-based treatments (EBTs) (Hogan, 2003). At present, efforts to implement EBTs largely rely on training clinicians in individual empirically-supported treatment manuals or protocols.…”
mentioning
confidence: 99%